Childhood trauma in bipolar disorder. (June 2014) - Watson, Stuart; Gallagher, Peter; Dougall, Dominic; Porter, Richard; Moncrieff, Joanna; Ferrier, I Nicol; Young, Allan H
Objective: There has been little investigation of early trauma in bipolar disorder despite evidence that stress impacts on the course of this illness. We aimed to compare the rates of childhood trauma in adults with bipolar disorder to a healthy control group, and to investigate the impact of childhood trauma on the clinical course of bipolar disorder. Methods: Retrospective assessment of childhood trauma was conducted using the Childhood Trauma Questionnaire (CTQ) in 60 outpatients with bipolar disorder being treated for a depressive episode and 55 control participants across two centres in north-east England and New Zealand. Results: Significantly higher rates of childhood trauma were observed in patients with bipolar I and bipolar II disorder compared to controls. Logistic regression, controlling for age and sex, identified emotional neglect to be the only significant CTQ subscale associated with a diagnosis of bipolar disorder. Childhood history of sexual abuse was not a significant predictor. Associations with clinical severity or course were less clear. Conclusions: Childhood emotional neglect appears to be significantly associated with bipolar disorder. Limitations include the relatively small sample size, which potentially increases the risk of type II errors. Replication of this study is required, with further investigation into the neurobiological consequences of childhood trauma, particularly emotional neglect.